The effect of pitting corrosion on the safe-life prediction of the Royal Australian Air Force P-3C Orion aircraft. (September 2015) - Shekhter, A.; Crawford, B.R.; Loader, C.; Hu, W.
Highlights: The effect of pitting on the fatigue life of the P-3C aircraft was investigated. This investigation used fatigue specimens containing a representative high- kt hole. Both experimental fatigue tests and analytical modelling approaches were used. The modelling compared the P3-C SLAP method with an equivalent crack size method. It was concluded that pitting did not invalidate the P3-C SLAP lifeing method. Abstract: This paper investigates if corrosion pitting invalidates the fatigue lifeing method used by the Royal Australian Air Force to manage the structural integrity of its P-3C Orion aircraft. Fatigue life predictions made using the P-3C Service Life Assessment Program method were compared with those from an Equivalent Crack Size model for pitting corrosion. The data for this comparison came from a program of variable amplitude fatigue tests of high- kt specimens of 7075-T6. This testing was performed using two stress levels on both corroded and uncorroded specimens. Analysis of the results showed that the safe-life estimates made using the P-3 life assessment method were conservative in the presence of corrosion as they were above the 99.9th percentile of fatigue life predicted by the equivalent crack size method.